Increasing the transmission capacity an inhomogeneous electrical network by regulating the equalizing EMF - A. I. Motovilov; I. I. Solovejev (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. Consideration of issues related to the study of ways to increase the capacity of the electrical network, characterized by the maximum transmitted power between the nodes of the electrical network. Switching in the electrical network and power imbalance in nodes during transmission of electricity are reasons of overloads and blackouts. To prevent overloads, the transmission volumes are reduced. It is the reason for a decrease in the reliability of power supply to consumers, the efficiency of using energy resources and disconnection of systems. In practice, the traditional methods of reducing network congestion are generation regulation, changing the network topology, and, if they are not enough, disconnecting consumers from the power grid.METHODS. Solving the problem, a computer model was used, created in the RastrWin3. This study transmission capacity of the electrical network with the taking influence equalizing EMF between the nodes of the power grid.RESULTS. The article describes the relevance problems, it is shown that the regulation of the equalizing EMF allows you to change the value of the maximum allowable power transmitted between the nodes of the electrical network. CONCLUSION. The results of the study can be used in the practice of dispatch control to solve problems of improving the reliability, planning and operating the power system in real time. The efficiency of the proposed algorithm is tested experimentally.